The prototypical approach to the analysis of the phenomenon of prejudices - Smirnova, Yuliya S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The prototypical approach to the analysis of the phenomenon of prejudices is analyzed in the article. The results of the empirical study of the prototypical content of the category «prejudice» are presented. The prototypical forms of prejudices are defined. In accordance with the results, racial, ethnic, professional and some other prejudices of high status majority against members of minority in the form of discrimination, aggression and contact limitation in the fields of employment and education, as well as in various social situations in public places are prototypical. The results’ application in prejudice reduction is discussed.